Acupuncture attenuates cognitive impairment, oxidative stress and NF-κB activation in cerebral multi-infarct rats. Issue 5 (October 2019) - Yang, Jing-Wen; Wang, Xue-Rui; Ma, Si-Ming; Yang, Na-Na; Li, Qian-Qian; Liu, Cun-Zhi
Backgroud: Patients with multiple infarct dementia (MID) have subtle deficits that commonly go unnoticed, and are at risk of developing Alzheimer's disease. Oxidative stress induced by ischaemic injury results in intracellular calcium accumulation and neuronal apoptosis, leading to cognitive impairment by triggering various cellular signal transduction pathways. Several studies have suggested that NF-κB in the presence of p53 has a pro-apoptotic function in various models, but the mechanism is unclear. Aims: The aim of this study was to investigate whether acupuncture could protect cognitive function against cerebral multi-infarction (CMi) induced oxidative stress by inhibiting the activation of NF-κB and its target gene p53. Methods: An animal model of CMi was established by injecting homologous blood emboli into the right internal carotid artery of male Wistar rats. After 2 weeks of acupuncture treatment, cognitive function was detected by novel object recognition. Electron spin resonance and Fluo-3 fuorescence imaging were used to test the generation of ROS and intracellular calcium accumulation, respectively. Expression of NF-κB and p53 was examined by Western blot analysis and immunofluorescence. Results: CMi induced spatial learning and memory impairment, overproduction of intracellular hydroxyl radicals, and elevations of Ca 2+, which were ameliorated by verum acupuncture treatment. Acupuncture inhibited activation of NF-κB and its downstream target gene p53. Conclusion: These findings suggest that acupuncture could protect cognitive function against oxidative stress induced by CMi, which is partially associated with suppression of NF-κB-p53 activation.